Woody forage species in the Sahel: Their biology and use - Bille, Jean-Claude (Society for Range Management, 1978)
Presents results of a study on trees and shrubs of a Sahelian site in Senegal, w. respect to aboveground biomass, productivity and consumption by livestock. Discusses the impact of the 1972 drought on various plant zones of the area.